Cuba in the World, the World in Cuba - Lorini, Alessandra (Firenze University Press, 2009)
The volume approaches Cuba as a nation that hosts a convergence of extraordinary global developments and, in turn, projects itself onto the world's major cultural, political and economic processes. From different perspectives, ranging from architecture and music to politics and economics, the twenty-one essays presented here embrace the multifaceted interactions between Cuba and foreign imperial strategies during the 19th century, the troublesome formation of national political cultures in the first half of the 20th century, and the multiple global aspects of some of Cuba's choices from the Cold War to the first decade of the present century.